IMPLIKASI PERDEBATAN TENTANG BASMALAH ATAS KEMUTAWATIRAN AL-QUR`AN - Mohammad Zahid (Faculty of Sharia IAIN Madura collaboration with The Islamic Law Researcher Association (APHI), 2015)
The ulama agreed that the inclusion of all sentences in the Qur`an must be based on riwâyat which is mutawâtir, so the truth can be guaranteed (qath`î wurûd âyi al-Qur'ân). It also happened to the word basmalah which always comes in the beginning of the Surah. Therefore, Maliki school refused to state that basmalah as the Qur`an’s sentence, because of the existence of some riwâyat ahâd which informed two different things: it is a part of the Qur`an and it is not. Actually riwâyat ahâd cannot be used to include a text to be a sentence of the Qur`an or to refuse it. While the majority of ulama’s point of view is not only based on some ahâd histories which stated that basmalah is a sentence of the Qur`an. The history facts in the process of jam`u al-Qur'ân (the gathering of the Qur`an) from the era of the prophet/Rasulullah, the year of Abû Bakr to the standardization of the Qur`an in the year of Utsmân bin `Affân confirmed that the companions of the prophets would never include or refuse a sentence, if it was only based on the ahâd history although its quality was shahîh. Therefore, the determination of the word of basmalah as a statement of the Qur`an, should not be based on the ahâd history only, but also supported with ijmâ` of the companions to the existence of Mushhaf Utsmânî or which is known as the source of history of mutawâtir `amalî.Copyright (c) 2016 by Al-Ihkam. All right reservedDOI: 10.19105/al-ihkam.v10i2.721